Modeling and Control of the Vibration of Two Beams Coupled with Fluid and Active Links - Zhiyi Zhang; Fang Hu; Zeng Li; Hongxing Hua (Shock and Vibration)
Investigated are modeling and control approaches for vibration analysis of two identical beams which are coupled with fluid and active mechanical links. In the modeling of the coupled beam system, orthogonal functions are used to represent vibration of the beams and the fluid-structure interaction is considered. Frequency Response Functions (FRFs) are derived from the coupled governing equations and the superposition principle for linear vibration systems. In the control of vibration of the beams, impulse response functions corresponding to the FRFs and an adaptive control algorithm are employed to attenuate vibration transmission between the two beams. Natural frequencies, mode shapes as well as the pressure distribution in the fluid are computed. The results obtained by the proposed modeling method are in good consistency with those obtained by the finite element analysis. Moreover, it is demonstrated that the active mechanical link is able to reduce vibration transmission and change the deformation of beams as well as the distribution of fluid pressure.